Post-Traumatic Stress Disorder in Indamā Qatalū Al-Rabi Novel - Zafirah Fitrie Adhiyantami; Ahfa Rahman Syah (Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2022)
This study analyzes Post-Traumatic Stress Disorder (PTSD) in the main character Bella in the Indamā Qatalū al-Rabi novel by Hiba Jamal As'ad. This research departs from the central issue of this novel, which is about situations of war, crime, and the oppression that befalls the main character Bella, which negatively impacts her psyche. This study applies a descriptive analysis method using PTSD theory which refers to the Diagnostic of Mental Disorders DSM V (Diagnostic and Statistical Manual of Mental Disorders Fifth Edition) by APA (American Psychiatric Association) to reveal personality, trauma, symptoms, and efforts to suppress PTSD disorders Bella character. The results show that Bella, who initially had positive characteristics such as being sociable and cheerful, transformed into a mentally and psychologically disturbed person due to her experiences of severe trauma such as the murder of her parents, rape, harassment, threats to spreading immoral videos, and some physical and mental violence. All of these experiences created PTSD disorders in Bella with symptoms of sleep disturbances, avoidance of certain situations and moments, and loss of the ability to feel emotional feelings or positive emotions. At the end of the story, Bella's marriage to Hassan becomes an important event and stimulus for Bella to reduce the stress and trauma.